Ethnography of Communication of the Jakun Tribe: (Etnografi Komunikasi Orang Asli Jakun) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2021)
This study discusses the ethnography of communication of Jakun tribes people in two villages in the sub-district of Kahang: Kampung Seri Kenangan and Kampung Punjut. The main objective of this study is to explain the ethnography of communication of the Jakun Tribe. Furthermore, this study uses a qualitative descriptive method to interpret the data collected in the field. The data was collected through interviews with 20 informants of Jakun tribes people. Description of the ethnography of communication of the Jakun language in this study employs the theoretical framework of SPEAKING introduced by Dell Hymes (1964). The SPEAKINGframework enable explanation of the communication event and background of the Jakun tribe.Keywords: Indigenous people, Jakun tribe, ethnography, communication, SPEAKING model